Cobalt-doped MoS2 nanocomposite with NADH oxidase mimetic activity and its application in colorimetric biosensing of NADH. (December 2021) - Zhang, Yujiao; Cai, Yuanyuan; Wang, Jin; Niu, Lingxi; Yang, Shuqing; Liu, Xuan; Zheng, Zongmei; Zeng, Lingxing; Liu, Aihua
Graphical abstract: Highlights: Co-MoS2 nanocomposite exhibiting NADH oxidase mimic activity. The mechanism of the NADH oxidase mimics was studied. Sensitive and selective colorimetric sensor for NADH developed. Abstract: NADH oxidase (NOX) is an oxidoreductase that catalyzes the oxidation of NADH to NAD + with the participation of oxygen. NOX can artificially regulate metabolic processes as an important regulatory enzyme for NAD + regeneration. In this study, cobalt-doped molybdenum sulfide (Co-MoS2 ) nanocomposite was prepared by hydrothermal synthesis, which exhibited NOX mimics. The catalytic mechanism of NOX mimics was studied. The NOX-like activity of Co-MoS2 is optimal at pH 4.5 and in the temperature range of 20–45℃. Further, its catalytic activity maintained almost the same after 5 cycles of repetitive addition of NADH, suggesting that Co-MoS2 nanozyme possessed significant catalytic persistence. The produced H2 O2 catalyzed by Co-MoS2 can be detected by horseradish peroxidase (HRP) and 3, 3′, 5, 5′-tetramethylbenzidine at pH4.5. Thus, interestingly, a colorimetric NADH sensor was proposed on the basis of the enzymatic cascade reaction of NADH oxidase-like conjugated with HRP. This as-established method had wide detection range (0.5–800 μM) with the detection limit of 0.25 μM NADH, capable of detecting NADH in real sample.